Association between physical health and cardiovascular diseases: Effect modification by chronic conditions. (4th July 2018) - Saquib, Nazmus; Brunner, Robert; Desai, Manisha; Allison, Matthew; Garcia, Lorena; Stefanick, Marcia L
Objectives: This study assessed whether the physical component summary score of the RAND-36 health-related quality-of-life survey was associated with incidence of coronary heart disease, stroke, congestive heart failure, angina, or peripheral arterial disease, and whether baseline chronic conditions modified these associations. Methods: Analysis was limited to 69, 155 postmenopausal women (50–79 years) in the Women's Health Initiative Study who had complete data on the RAND-36, the outcomes, and covariates. Chronic conditions were defined as blood pressure ⩾140/90 mm or self-reported heart disease, diabetes, hypertension, arthritis, asthma, emphysema, cancer, and/or cholesterol-reducing medication use. Outcomes data were ascertained during follow-up (1993–2005) with medical records. Results: There were 2451 coronary heart disease, 1896 stroke, 1533 congestive heart failure, 1957 angina, and 502 peripheral arterial disease events during follow-up (median 8.2 years). Participants in the lowest physical component summary quintile, compared to the highest, had a significantly higher risk of developing coronary heart disease (hazard ratio (95% confidence interval) 2.0 (1.7, 2.3)), stroke (1.8 (1.5, 2.2)), angina (2.4(2.0, 2.9)), and peripheral arterial disease (3.0 (2.0, 4.4)), irrespective of chronic conditions. Interactions between physical component summary and existing chronic conditions were not significant for any outcome except congestive heart failure (p = 0.005); after adjustment, participants in the lowest physical component summary quintile and with any chronic condition had nearly a twofold higher risk of congestive heart failure (Yes = 4.4 (3.3, 5.8) vs No = 2.4 (1.2, 4.3)). Conclusion: We found a low physical component summary score was a significant risk factor for individual cardiovascular disease incidence in postmenopausal women.